The Economics of Fairness, Reciprocity and Altruism - Experimental Evidence and New Theories - Ernst Fehr; Klaus M. Schmidt (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
Chapter written for the Handbook of Reciprocity, Gift-Giving and Altruism
urn:nbn:de:bvb:19-epub-13484-7
Keywords: C7; C9; D0; J3; 330; Behavioural Economics; Other-regarding Preferences; Fairness; Reciprocity; Altruism; Experiments; Incentives; Contracts; Competition